Atypical presentation of anti-NXP-2 positive juvenile dermatomyositis - Andreia Coimbra-Sousa; Renata Miossi; Fernando H. C. de Souza; Samuel Katsuyuki-Shinjo (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Dear Editor, The anti-NXP-2 is one of a myositis-specific autoantibody considered a marker of dermatomyositis (DM)1,2. In addition, there is a strong relationship between NXP-2 autoantibodies and calcinosis, particularly in juvenile DM2.